Private Sector-led Urban Development Projects: Management, Partnerships and Effects in the Netherlands and the UK - Heurkens, Erwin (A+BE | Architecture and the Built Environment, 2012)
Central to this research lays the concept of private sector-led urban development projects (Heurkens, 2010). Such projects involve project developers taking a leading role and local authorities adopting a facilitating role, in managing the development of an urban area, based on a clear public-private role division. Such a development strategy is quite common in Anglo-Saxon urban development practices, but is less known in Continental European practices. Nonetheless, since the beginning of the millennium such a development strategy also occurred in the Netherlands in the form of ‘concessions’. However, remarkably little empirical knowledge is available about how public and private actors collaborate on and manage private sector-led urban development projects. Moreover, it remains unclear what the effects of such projects are. This dissertation provides an understanding of the various characteristics of private sector-led urban development projects by conducting empirical case study research in the institutional contexts of the Netherlands and the UK. The research provides an answer to the following research question: What can we learn from private sector-led urban development projects in the Netherlands and UK in terms of the collaborative and managerial roles of public and private actors, and the effects of their (inter)actions? Indications for a market-oriented Dutch urban development practice Urban development practice in the Netherlands has been subject to changes pointing towards more private sector involvement in the built environment in the past decades. Although the current economic recession might indicate otherwise, there are several motives that indicate a continuation of private sector involvement and a private leadership role in Dutch urban development projects in the future. First, a shift towards more market-oriented development practice is the result of an evolutionary process of increased ‘neoliberalization’ and the adoption of Anglo-Saxon principles in Dutch society. Despite its Rhineland roots with a focus on welfare provision, in the Netherlands several neoliberal principles (privatization, decentralization, deregulation) have been adopted by government and incorporated in the management of organizations (Bakker et al., 2005). Hence, market institutionalization on the one hand, and rising civic emancipation on the other, in current Western societies prevents a return towards hierarchical governance. Second, the result of such changes is the emergence of a market-oriented type of planning practice based on the concept of ‘development planning’. Public-Private Partnerships and the ‘forward integration’ of market parties (De Zeeuw, 2007) enforce the role of market actors. In historical perspective, Boelens et al. (2006) argue that Dutch spatial planning always has been characterized by public-private collaborations in which governments facilitated private and civic entrepreneurship. Therefore, post-war public-led spatial planning with necessary government intervention was a ‘temporary hiccup’, an exception to the rule. Third, the European Commission expresses concerns about the hybrid role of public actors in Dutch institutionalized PPP joint ventures. EU legislation opts for formal public-private role divisions in realizing urban projects based on Anglo-Saxon law that comply with the legislative tendering principles of competition, transparency, equality, and public legitimacy. Fourth, experiences with joint ventures in the Netherlands are less positive as often is advocated. Such institutionalized public-private entities have seldom generated the assumed added value, caused by misconceptions about the objectives of both partners grounded in incompatible value systems. This results in contra-productive levels of distrust, time-consuming partnership formations, lack of transparency, and compromising decision-making processes (Teisman & Klijn, 2002), providing a need for other forms of collaboration. Finally, current financial retrenchments in the public sector and debates about the possible abundance of Dutch active land development policies point towards a lean and mean government that moves away from risk-bearing participation and investment in urban projects and leaves this to the market. Importantly, Van der Krabben (2011b) argues that the Dutch active public land development policies can be considered as an international exception, and advocates for facilitating land development policies. In this light, it becomes highly relevant to study private sector-led urban development as a future Dutch urban development strategy. Integrative urban management approach This research is rooted in the research school of Urban Area Development within the Department of Real Estate and Housing at the Faculty of Architecture (Delft University of Technology). It is a relatively young academic domain which views urban development most profoundly as a complex management assignment (Bruil et al., 2004; Franzen et al., 2011). This academic school uses an integrative perspective with a strong practice-orientation and carries out solution-oriented design research. Here, the integration involves bridging various actor interests, spatial functions, spatial scales, academic domains, knowledge and skills, development goals, and links process with content aspects. Such a perspective does justice to complex societal processes. Therefore it provides a fruitful ground for studying urban development aimed at developing conceptual knowledge and product for science and practice. Such integrative perspective and practice-orientation forms the basis of this research and has been applied in the following manner. In order to create an understanding of the roles of public and private actors in private sector-led urban development, this research takes a management perspective based on an integrative management approach. This involves viewing management more broadly as ‘any type of direct influencing’ urban development projects, and therefore aims at bridging often separated management theories (Osborne, 2000a). Hence, an integrative management approach assists in both understanding urban development practices and projects and constructing useful conceptual tools for practitioners and academics. Integrative approaches attempt to combine a number of different elements into a more holistic management approach (Black & Porter, 2000). Importantly, it does not view the management of projects in isolation but in its entire complexity and dynamics. Therefore, our management approach combines two integrative management theories; the open systems theory (De Leeuw, 2002) and contingency theory. The former provides opportunities to study the management of a project in a structured manner. The latter emphasizes that there is no universally effective way of managing and recognizes the importance of contextual circumstances. Hence, an integrative management approach favors incorporating theories from multiple academic domains such as political science, economics, law, business administration, and organizational and management concepts. Hence, it moves away from the classical academic division between planning theory and property theory, and organization and management theories. It positions itself in between such academic domains, and aims at bridging theoretical viewpoints by following the concept of planning ánd markets (Alexander, 2001) rather than concepts such as ‘planning versus markets’, public versus private sector, and organization versus management. Also, such an integrative view values the complexity and dynamics of empirical urban development practices. More specifically, this research studies urban development projects as object, as urban areas are the focus point of spatial intervention and public-private interaction (Daamen, 2010), and thus collaboration and management. Here, public planning processes and private development processes merge with each other. Thus, our research continues to build upon the importance of studying and reflecting on empirical practices and projects (e.g. Healey, 2006). In addition to these authors, this research does so by using meaningful integrative concepts that reflect empirical realities of urban projects. Thereby, this research serves to bridge management sciences with management practices (Van Aken, 2004; Mintzberg, 2010) through iterative processes of reflecting on science and practice. Moreover, the integrative management approach applied in this research assists in filling an academic gap, namely the lack of management knowledge about public-private interaction in urban development projects. Despite the vast amount of literature on the governance of planning practices (e.g. DiGaetano & Strom, 2003), and Public-Private Partnerships (e.g. Osborne, 2000b), remarkable little knowledge exists about what shifting public-private relationships mean for day-to-day management by public and private actors in development projects. Hence, here we follow the main argument made by public administration scholar Klijn (2008) who claims that it is such direct actor influence that brings about the most significant change to the built environment. An integrative urban management model (see Figure 2.3) based on the open systems approach has been constructed which forms a conceptual representation of empirical private sectorled urban development projects. This model serves as an analytical tool to comprehend the complexity of managing such projects. In this research, several theoretical insights about publicprivate relations and roles are used to understand different contextual and organizational factors that affect the management of private sector-led urban development projects. Hence, a project context exists within different often country-specific institutional environments (e.g. the Netherlands and UK). In this research, contextual aspects that to a degree determine the way public and private actors inter-organize urban projects, consist of economics & politics, governance cultures, and planning systems and policies. Hence, institutional values are deeply rooted in social welfare models (Nadin & Stead, 2008). For instance, the differences between Anglo-Saxon and Rhineland model principles also determine public-private relationships. However, the process of neoliberalization (Hackworth, 2007) and subsequent adaptation of neoliberal political ideologies (Harvey, 2005) has created quite similar governance arrangements in Western countries. Nevertheless, institutional rules incorporated in planning systems, laws and policies often remain country-specific. But, market-oriented planning, involving ‘planners as market actors’ (Adams & Tiesdell, 2010) intervening and operating within market systems, have become the most commonly shared feature of contemporary Western urban development practices (Carmona et al., 2009). In this research, the project organization focuses on institutional aspects and interorganizational arrangements that structure Public-Private Partnerships (Bult-Spiering & Dewulf, 2002). It involves studying organizational tasks and responsibilities, financial risks and revenues, and legal rules and requirements. Inter-organizational arrangements condition the way public and private actors manage projects. Hence, such arrangements can be placed on a public-private spectrum (Börzel & Risse, 2002) which indicates different power relations in terms of public and private autonomy and dominance (Savitch, 1997) in making planning decisions. These public-private power relations are reflected in different Public-Private Partnership arrangements (Bennet et al., 2000) in urban development projects. As a result, in some contexts these partnerships arrangements are formalized into organizational vehicles or legal contracts, in others there is an emphasis on informal partnerships and interaction. The lack of management knowledge on private sector-led urban development projects, and our view of management as any type of direct influencing, results in constructing a conceptual public-private urban management model (see Figure SUM.1). This model is based on both theoretical concepts and empirical reflection. In this research, the management of project processes by public and private actors contains applying both management activities and instruments. Project management (Wijnen et al., 2004) includes development stage-oriented initiating, designing, planning, and operating activities. Process management (Teisman, 2003) includes interaction-oriented negotiating, decision-making, and communicating activities. Management tools consist of legal-oriented shaping, regulating, stimulating, and capacity building planning tools (Adams et al., 2004). And management resources consist of crucial necessities (Burie, 1978) for realizing urban projects like land, capital and knowledge. In essence, all these management measures can be applied by public and private actors to influence (private sector-led) urban development projects. These management measures can be used by actors to reach project effects. In this research, project effects are perceived as judgment criteria for indicating the success of the management of private sector-led urban development projects. They consist of cooperation effectiveness, process efficiency, and spatial quality. Effectiveness involves the degree to which objectives are achieved and problems are resolved. Ef ficiency is the degree to which the process is considered as efficiently realizing projects within time and budget. Finally, spatial quality is the degree to which the project contributes to responding to user, experience and future values of involved actors (Hooijmeijer et al., 2001). Such process and product effects are a crucial addition to understand the results of private sector-led urban development projects. Comparative case study research using a lesson-drawing method This research systematically analyzes and compares private sector-led urban development cases in both the Netherlands and the UK in a specific methodological way. In essence, this study is an empirical comparative case study research using a lesson-drawing method. Hence, case studies allow for an empirical inquiry that investigates a contemporary phenomenon within its real life context (Yin, 2003). Such a qualitative approach is very suited for the purposes of this research as it enables revealing empirical collaborative and managerial mechanisms within private sector-led urban development projects. The reason to include studying the UK lies is the fact that it can be considered as a market-oriented development practice, from which valuable lessons can be drawn for the Netherlands. Thereby, this research places itself in a longer tradition of Dutch interests in UK planning and development (e.g. Hobma et al., 2008). Hence, this research aims at drawing lessons in the form of ‘inspiration’ from practices and projects, as opposed to the more far-reaching transplantation of spatial policies (e.g. Janssen-Jansen et al., 2008). However, in order to draw meaningful empirical lessons there is a need to indicate whether they are context-dependent or -independent. This requires systematically comparing the institutional planning practices of both countries by indicating differences and similarities between the Netherlands and the UK. Based on these methodological principles ten Dutch and two UK of private sector-led urban development cases are selected and studied. The Dutch cases focus on scope over depth aimed at sketching the phenomenon of ‘area concessions’ in both inner-city and urban fringe projects. The UK cases focus on depth over scope aimed at understanding the applicability of a private sector-led approach in complex large-scale inner-city projects. As techniques the case study research uses document reviews, semi-structured interviews, project visits, and data mapping. Comparing Dutch and UK planning and urban development practices The institutional context of urban development in the Netherlands and the UK shows some structural differences, despite the fact that such contexts are often subject to change. For instance, the Dutch planning system uses Napoleonic codified law based on a constitution with abstract law principles as rule, and a limited role of judicial power. The UK planning system is based on British common law lacking a constitution, and uses law-making-as-we-go as judges act as law-makers. In terms of spatial planning, the Netherlands is characterized by binding land use plans within a limited-imperative system based on legal certainty. Dutch spatial planning can be labelled as ‘permitted planning’ based on ‘comprehensive integrative model’ (Dühr et al., 2010) which involves hierarchically coordinated and related public sector spatial plans. UK spatial planning has no binding land use plan, places importance on material considerations based on discretionary authority and flexibility. Historically, UK’s spatial planning can be labelled as ‘development-oriented planning’ based on a ‘land use management model’ with a focus on public sector coordinated planning policies. Moreover, Dutch and UK urban development also differ in terms of public and private roles in organizing and managing development (Heurkens, 2009). In the Netherlands, local governments are active bodies using spatial plans, active land development policies and public investment to develop cities. The private sector often operates reactively and is historically focused on the physical realization of projects. In general, public-private decision-making processes are based on reaching consensus, development project coordination typically involves ‘collaboration models’, and management is focused on process as product outcomes. In the UK, local government uses relatively less regulations and investment to develop cities, thereby facilitating market parties. The development industry is a mature sector, actively initiating and investing in projects. Decision-making is characterized by negotiations, and the organization of projects is often based on a clear formal public-private role division. Despite such a generic Dutch-UK comparison being of crucial importance to this research, it does no justice to increasing similarities between European planning practices. Moreover, such institutional contexts evolve as a result of changing planning priorities in each country. For instance, some basic characteristics of the UK planning system attracted the attention of Dutch planners, including comprehensive principles for project coordination, private sector involvement and negotiations, options for the settlement of ‘planning gain’, packaging interests, development-oriented planning, and discretion for planning decisions (Spaans, 2005). Hence, such more market-oriented planning principles have become valuable and sometimes necessary mechanisms to effectively cope with an increasingly less public-led and more private sector-led Dutch urban development practice. Empirical findings from Dutch private sector-led urban development cases Urban development practice in the Netherlands since the year 2000 witnessed an increased use of the concession model. Hence, this is the Dutch definition for private sector-led urban development. It can best be characterized as a contract form between public and private parties which involves the transfer of risks, revenues, responsibilities for the plan, land and real estate development to private developers based on pre-defined set of public requirements (Gijzen, 2009). In theory (Van Rooy, 2007; Van de Klundert, 2008; Heurkens et al., 2008) this collaboration model holds promising advantages of being a more effective, efficient and transparent strategy to achieve a high quality built environment. Nonetheless, possible disadvantages like the lack of public ‘steering’, dependency of market actors and circumstances, inflexible contracts, a project management orientation, and a stern public-private relationship also are mentioned. Moreover, conditions for the application of concessions in theory involve a manageable project scale and duration, minimal political and societal complexity, and maximum freedom for private actors. Motives for choosing concessions are the lack of public labor capacity and financial development means, risk transfer to private actors, increasing private initiatives and private land ownership. Hence, in theory public and private roles in the concession model are considered as strictly separated. However, there is a lack of structural empirical understanding and evidence for such theoretical assumptions. Therefore, empirical cases in Amsterdam, The Hague, Enschede, Maassluis, Middelburg, Naaldwijk, Rotterdam, Tilburg, Utrecht, and Velsen (see Table 5.1) are carried out. This includes studying private sector-led projects in both inner-city and urban fringe locations. The main conclusions based on cross-case study findings of these ten Dutch projects are highlighted here. Notice that public-private interaction and collaboration remains of vital importance in Dutch private sector-led urban development projects. Despite the formal contractual separation of public and private tasks and responsibilities, in practice close informal cooperation can be witnessed, especially in the early development stages. Moreover, public actors do not remain as risk free as theory suggests, because unfavorable market circumstances can cause development delays affecting the living environment of inhabitants. Furthermore, it seems that constructing and using flexible public requirements with some non-negotiable rules is an effective condition for realizing public objectives during the process. In terms of management, most projects are hardly considered as solely private sector-led, as they involve a substantial amount of public management influence. For instance, project management activities include a dominant role of municipalities in initiating and operating the development. Process management activities are carried out by both actors, as they involve close public-private interactions. Management tools are mostly used by public actors to shape and regulate development with a limited conscious usage of stimulating and capacity building tools. Using the management resources land, capital and knowledge are mainly a private affair. In terms of effects, the concession model by actors is considered as an effective instrument, but not necessarily results in efficient processes. The general perception of public, private and civic actors about the project’s spatial quality level is positive. In addition, actors were asked about their cooperation experiences. Often mentioned problems include a ‘we against them relationship’, lack of public role consistency, thin line between plan judgment and control, public manager’s commitment and competency, communication with local communities, and lack of public management opportunities. Based on the empirical case studies, most conditions for applying concessions are confirmed. However, the successful inner-city development projects in Amsterdam and Enschede indicate that a private sector-led approach can also be applied to more complex urban development projects within cities. Empirical findings from UK’s private sector-led urban development cases Urban development practice in the UK often is labelled as urban regeneration. Historically, it is strongly shaped by neoliberal political ideology of the Conservative Thatcher government in the 1980s. But it also is influenced by New Labour ideologies favoring the Third Way (Giddens, 1998) aimed at aligning economic, social and environmental policies. However, as a result of these institutional characteristics, the UK is strongly shaped by the understanding that most development is undertaken by private interests or by public bodies acting very much like private interests (Nadin et al., 2008). In general, local authorities depend on initiatives and investments of property developers and investors, because public financial resources and planning powers to actively develop land are limited. As a result, development control of private developments is a concept deeply embedded in development practice. Several legal instruments such as Section 106 agreements are used to establish planning gain by asking developer contributions for public functions. Moreover, urban development in the UK has a strong informal partnership culture, and simultaneously builds upon a strict formal legal public-private role division. These UK urban development practice characteristics provide valid reasons to study private sector-led urban development projects in more detail. The empirical cases of private sector-led urban development projects in the UK are Bristol Harbourside and Liverpool One. They represent mid-2000s strategic inner-city developments with a mixed-use functional program, and therefore possible high complexity. As such, they are relevant urban projects for drawing lessons for the Netherlands. The main conclusions based on cross-case study findings of the UK projects are discussed here. The case contexts show that politics and the often changeable nature of planning policies can have a major influence on the organization and management of development projects. Hence, strong and effective political leadership is considered as a crucial success factor. Changing policies result in re-establishing development conditions resulting in new publicprivate negotiations. In terms of organization, the cases indeed show that local authorities do not take on development risks. Moreover, revenue sharing with private actors is absent or limited to what the actors agree upon in development packages. Furthermore, local authorities encourage all kinds of partnerships with other public, private or civic stakeholders in order to generate development support and raise funds. In terms of management, local authorities use different management measures to influence projects. The cases indicate that public actors are able to influence private sector-led developments and thereby achieve public planning objectives. Importantly, public actors use all kinds of managing tools to shape and stimulate development; they do not limit themselves to regulation but also build capacity for development. However, the largest share of managing the project takes place on behalf of project developers. Private actors manage projects from initial design towards even public space operation (Liverpool). Thereby, they work with long-term investment business models increasing private commitment. In terms of effects, the cases show that although the projects are carried out effectively and achieve high quality levels, the process efficiency lacks behind due to lengthy negotiations. In conclusion, the actors’ experiences with the private sector-led urban development projects indicate some problems including; the financial dependency on private actors, lack of financial incentives for public actors, lack of awareness of civic demands, lack of controlling public opposition, long negotiation processes, and absence of skilled public managers. Moreover, the actors indicate some crucial conditions for a private sectorled approach including; flexible general public guidelines, informal partnerships and joint working, public and private leadership roles and skills, professional attitude and long term commitment of private actors, involvement of local communities, separating public planning and development roles, handling political pressures, and favorable market circumstances. Empirical lessons, improvements and inspiration Some general conclusions from the Dutch and UK case comparison can be drawn (see Table 8.1). The influence of the project’s context in the UK seems to be higher than in the Netherlands, especially political powers and changeable policies influence projects. The organizational role division in UK projects seems to be stricter than in the Dutch projects, where public requirements sometimes are also formulated in more detail. The actor’s management in the Dutch cases is slightly less private sector-led than in the UK, where local authorities and developers are more aware of how to use management measures at their disposal. The project effects show quite some resemblance; effectiveness and spatial quality can be achieved, while efficiency remains difficult to achieve due to the negotiation culture. Here, important empirical lessons learned from cases in both countries are discussed aimed at formulating possible solutions for perceived Dutch problems. The problematic Dutch ‘we against them relationship’ between actors in the UK is handled by a close collaboration. Developers organize regular informative and interactive design meetings with local authorities, sharing ideas in a ‘joint-up working’ atmosphere. The lack of public role consistency in the UK is resolved by local authorities that develop a clear schedule of spatial requirements which provides certainty. Moreover, room for negotiations allows for the flexibility to react on changed circumstances. The thin line between judgment and control of plans is not commonly recognized in the UK cases. Local authorities tend to respect that developers need room to carry out development activities on their own professional insights, and merely control if developers deliver ‘product specifications’ in time and to agreed conditions. The commitment and competencies of public project managers are also mentioned as crucial factors in the UK. It involves managers connecting the project to the political and civic environment, and leaders committing themselves to project support through communication with local communities. The lack of public management seems to be a Dutch perceived difficulty as UK local authorities do not apply active land development policies and ‘hard’ management resources. Therefore, they influence development with both more consciously applied legal tools and ‘soft’ management skills such as negotiating. Recommended improvements mentioned by Dutch practitioners here are mirrored to possible support from the UK cases. The Dutch recommendation to cooperate in pre-development stages to create public project support and commitment finds support in the UK. Hence, despite a formal division of public and private responsibilities, in practice a lot of informal public-private interaction and collaboration takes place and seems necessary. Striving for public role consistency also is an appreciated value by developers in the UK. Working on the principle of ‘agreement is agreement’ creates certainty for developers, and less resistance and willingness to cooperate once highly relevant public issues are put on the table. Establishing clear process agreements with moments of control or discussion in the UK are handled with evaluation moments aimed at judging output, and planned meetings aimed at creating a dialogue about new insights. Connecting planning and development processes in the UK is handled by a municipal team consisting of political leaders and project managers that align development processes with administrative planning processes. A clear communication plan to involve local communities and businesses in the UK is handled by developers which involve relevant stakeholders in the decision-making process prior to planning applications for support and process efficiency. Finding public opportunities to influence development other than land and capital in the UK is handled through the use of several public planning tools and publicprivate negotiations. The UK cases also provided various inspirational lessons for the Netherlands. First, the construction and application of a public ‘management toolbox’ consisting of various planning tools that shape, stimulate, regulate and activate the market could assist local authorities to view management more integratively and use existing instruments more consciously. Second, choosing a private development partner with professional expertise, track record and local knowledge, instead of an economically lucrative private tender offer for private sector-led urban development projects, has the advantage of creating a cooperative relationship. The reason for this is that flexible development concepts rather than fixed development plans are indicators of a cooperative attitude of a developer. Third, enabling partnership agreements between public, private and civic actors aimed at creating wide support and long-term commitment by expressing development intentions assists pulling together development resources from both investors and central government. Fourth, privately-owned public space based on a land lease agreement containing public space conditions creates several financial advantages. For local authorities it eliminates public maintenance costs, and for private actors the operation of the area and maintaining high quality standards can be beneficial for real estate sales and returns. Fifth, the value increase-oriented investment model of a long-term private development investor rather than a short-term project-oriented developer with a trade-off model between time, costs and quality has advantages. Large amounts of upfront investment can more easily be financed as high quality environments and properties increase the area’s competitive position and investment returns. Sixth, local authorities can establish partnerships that actively apply for public funding alternatives such as lottery funds. Such funds secure the development of public functions and create interest for commercial actors to invest, which can result possibilities to negotiate development packages which can results in a planning gain for public actors. Seventh, public and private leadership styles on different organizational levels for inner-city development projects result in more efficient processes. Appointing strategictactical operating political leaders and private firm directors and tactical-operational public and private project leaders streamlines internal and external communication and shared project commitment and support. Finally, the UK shows that a private sector-led approach can successfully be applied to complex inner-city developments. Despite the complex social and political character, fragmented land ownership situation, and high remediation costs UK developers can deliver such projects succesfully. Conditions seem a professionally skilled and financially empowered developer, and active local authorities that facilitate market initiatives. The likelihood of transfer of the inspirational UK lessons depends on some Dutch institutional characteristics (economics & politics, governance culture, planning system and policies). However, most lessons are context-independent and thus can be applied in the Dutch urban development practice. But, Table 8.2 also shows some institutional context-dependent features that limit the transfer of UK findings to the Netherlands. This includes the general short-term scope of Dutch developers and the general wish from municipalities to hold ‘control’ over development projects. Reflections on safeguarding public interests & alternative financing instruments The epilogue contains conceptual reflections about alternative ways for safeguarding public interests and private financing instruments in line with the current social-economic climate. These reflections are not based on research findings but on an additional literature review that provides food for thought for public and private actors in urban development. Hence, safeguarding public interests is an important concern for public actors, especially in market-oriented planning and private sector-led urban development projects. In our pluralistic society it has become impossible for one actor to determine the public interest in all occasions. In line with societal development it would not only be socially-coherent for governments to engage private and civic actors in safeguarding public interests, but even a social necessity. Consciously applying different public interest safeguarding strategies based on both hierarchical, market and network mechanisms (De Bruijn & Dicke, 2006) provide this opportunity. By using a combination of legitimized hierarchical mechanisms, competitionoriented market mechanisms, and inter-action oriented network mechanisms, public values become institutionalized in private and civic sectors. Then, the role of public planning institutions in safeguarding increasing economic values, social cohesion and public health is to use both legitimate planning tools and accountable planning activities. It enables other actors to become both more responsible for and involved in their own built environment. In market-oriented planning and private sector-led urban projects, safeguarding public interest instruments include non-negotiable general planning standards which secure basic needs of civilians, and negotiable development conditions which create involvement of other actors. Non-negotiable safeguarding instruments include; public tender requirements, land use plans, planning permissions and financial claims. Negotiable safeguarding instruments include; contractual conditions, competitive dialogues, spatial quality plans, developer contributions, development incentives, performance indicators, and ownership (see Figure 10.2). The reliance of private investment in private sector-led urban development projects asks for exploring alternative financing instruments for urban projects with less reliance on credit capital. This is a crucial subject being the result of the effect the current economic situation has on the land and property market. Hence, it is widely acknowledged that in many development practices around the globe property investment for urban development has changed radically as a result of the international credit crisis and economic downturn (Parkinson et al., 2009). ‘New financial models’ have the attention of several Dutch practitioners (e.g. Van Rooy, 2011) and academics (e.g. Van der Krabben, 2011b). In the current Dutch urban development practice, one notices an increased interest in demand-driven development strategies promoting; bottom-up development initiatives, value-oriented investment strategies, and de-risked phasing of development, which potentially increase the feasibility of urban projects. A literature review indicates promising alternative financing instruments for Dutch urban development practice and private sector-led urban development projects, including; Tax Increment Financing, Temporary Development/Investment Grants, Lottery Funds, DBFM/ Concession Light, Crowd Funding, Urban Development Trusts, Business Improvement Districts, and Urban Reparcelling. These instruments have different features such as investment source, development incentives, organizational requirements and object conditions, which need to be taken into account by public and private actors once applied (see Table 10.3).